A heat-crosslinkable prepolymer powder and a preparation method thereof, a semi-solid gel electrolyte and application

CN122878489APending Publication Date: 2026-10-09HEFEI QIANRUI TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611399324.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-10
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

(1)常规凝胶体系中单体或聚合物前驱体添加量通常较高,多为5wt%-20wt%,会稀释基础电解液,降低有效离子传输能力;

Benefits of technology

(1)本发明以甲基丙烯酸缩水甘油酯为骨架单体,利用其甲基丙烯酸酯双键参与自由基共聚反应,作为后续交联反应位点,实现功能侧链引入和凝胶网络构筑,使预聚物粉末兼具结构可设计性、粉末可加工性和后续可交联性;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122878489A_ABST
    Figure CN122878489A_ABST
Patent Text Reader

Abstract

This invention relates to the field of battery technology, specifically disclosing a thermally crosslinkable prepolymer powder, its preparation method, a semi-solid gel electrolyte, and its applications. The prepolymer powder comprises a polymer backbone formed by the copolymerization of glycidyl methacrylate and a fluorinated functional monomer. The backbone retains epoxy functional side groups and is connected to at least one functional side chain selected from fluorinated alkyl ester side chains, fluorinated amide side chains, and perfluoroaryl side chains. During preparation, the two types of monomers are copolymerized under the action of a free radical initiator, and the degree of polymerization is controlled. After prepolymerization, the thermally crosslinkable prepolymer powder is obtained through post-treatment. When this powder is added to a basic liquid electrolyte, in-situ ring-opening crosslinking occurs under the action of the active components, utilizing epoxy groups to form a semi-solid gel electrolyte. This prepolymer powder possesses both processability and storage properties as well as secondary thermal crosslinking characteristics, significantly improving the interface stability, high voltage tolerance, and cycle performance of high-nickel ternary fast-charging lithium-ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, and in particular to a thermally crosslinkable prepolymer powder, its preparation method, a semi-solid gel electrolyte, and its applications. Background Technology

[0002] Currently, commercial lithium-ion batteries primarily utilize liquid electrolyte systems. Liquid electrolytes possess high room-temperature ionic conductivity and good electrode wetting capabilities. However, under conditions of high-nickel ternary cathodes, high-voltage operating ranges, and fast charging at 2C and above, liquid electrolytes are prone to continuous side reactions at the electrode interface. This leads to problems such as electrolyte oxidation and decomposition, instability of the SEI and CEI films, increased interfacial impedance, uneven lithium-ion migration, and rapid capacity decay during cycles. Particularly in the high-nickel 811 ternary cathode system, the cathode surface exhibits strong oxidizing properties, making it easier to induce electrolyte decomposition and interfacial structure degradation during high-rate charge and discharge. When combined with fast charging conditions, the migration rate of lithium ions in the electrolyte, electrode pores, and interfacial films is even higher, significantly increasing interfacial impedance. Ultimately, this results in more pronounced problems such as intensified polarization, decreased capacity retention, and shortened cycle life.

[0003] To address these issues, researchers often incorporate small-molecule polymeric monomers, crosslinking agents, polymer precursors, or thickeners into liquid electrolytes, typically using traditional gel electrolytes or semi-solid electrolytes, followed by thermal, photo, or chemical initiation to form a gel network. However, this type of system still suffers from the following shortcomings: (1) In conventional gel systems, the amount of monomer or polymer precursor added is usually high, mostly 5wt%-20wt%, which will dilute the base electrolyte and reduce the effective ion transport capacity. (2) Functional monomers or additives are mostly added in the form of physical blending, which can easily lead to problems such as migration, phase separation, precipitation or uneven local distribution in the electrolyte; (3) Residual small molecule monomers may increase the risk of side reactions inside the cell and affect long-term cycle stability; (4) Some gel systems rely on high cross-linking density to obtain mechanical stability, but excessively high cross-linking density will limit the fluidity of electrolyte and lithium ion migration channels, which is not conducive to further improvement of 2C fast charging performance; In summary, existing systems typically struggle to simultaneously achieve electrode interface stability, high voltage tolerance, lithium-ion migration regulation, and rapid in-situ gelation under low addition levels.

[0004] Therefore, there is an urgent need to develop a prepolymer powder that simultaneously possesses the following characteristics: first, it contains functional side chains that can improve interfacial stability and high voltage stability; second, it has active functional groups that can participate in subsequent in-situ crosslinking reactions and form a stable gel network under electrolyte environment and thermally promoted conditions; third, it can be stably stored and added to the electrolyte in powder form; and fourth, it can achieve effective gelation at low addition levels and is suitable for fast-charging ternary lithium-ion battery systems. Summary of the Invention

[0005] To address the technical problems existing in the background art, the present invention proposes a thermally crosslinkable prepolymer powder, wherein the thermally crosslinkable prepolymer powder comprises a polymer backbone formed by copolymerization of glycidyl methacrylate and fluorinated functional monomers; The polymer backbone retains epoxy functional side groups; The polymer backbone is connected to a functional side chain, which is selected from at least one of fluoroalkyl ester side chains, fluoroamide side chains, and perfluoroaryl side chains.

[0006] In this invention, the prepolymer powder uses GMA as the core backbone monomer and undergoes free radical copolymerization with fluorine-containing functional monomers to form a prepolymer structure containing epoxy functional side groups and functional side chains. After the resulting prepolymer powder is added to a liquid electrolyte, under the promoting effect of active components such as LiDFOB and thermal conditions, the epoxy functional side groups undergo an in-situ ring-opening crosslinking reaction to form a continuous three-dimensional semi-solid gel electrolyte network. On the one hand, it can fix part of the liquid electrolyte, reducing electrolyte free migration and interfacial side reactions; on the other hand, it can still retain the high ion transport capacity of carbonate electrolyte, thus making it suitable for 2C fast-charging ternary systems.

[0007] Preferably, the number-average molecular weight Mn of the thermally crosslinkable prepolymer powder is 3000-20000 g / mol, the weight-average molecular weight Mw of the thermally crosslinkable prepolymer powder is 8000-60000 g / mol, and the molecular weight distribution PDI of the thermally crosslinkable prepolymer powder is 1.5-3.5.

[0008] Preferably, the particle size of the thermally crosslinkable prepolymer powder is 1-20 μm; the D50 of the thermally crosslinkable prepolymer powder is 3-8 μm.

[0009] In this invention, the obtained thermally crosslinkable prepolymer powder is a light white to slightly yellow free-flowing powder with good dispersibility, flowability and electrolyte wettability. The residual monomer content of the prepolymer powder is not higher than 1.0 wt%, and the moisture content is not higher than 200 ppm.

[0010] The present invention also proposes a method for preparing the above-mentioned thermally crosslinkable prepolymer powder, comprising the following steps: S1. Glycidyl methacrylate, fluorinated functional monomer, free radical initiator and organic solvent are mixed and prepolymerized under an inert atmosphere. The polymerization conversion rate is controlled at 10-50%. By controlling the degree of polymerization, a fluorinated prepolymer solution with epoxy functional side groups is obtained. S2. The solution of fluorinated prepolymer containing epoxy functional side groups is concentrated and precipitated. The precipitate is then washed, dried, crushed, and sieved to obtain the thermally crosslinkable prepolymer powder.

[0011] In step S1, the polymerization reaction uniformly introduces fluorine-containing functional monomer structural units into the glycidyl methacrylate polymer chain segments to obtain a prepolymer solution containing epoxy functional side groups and functional side chains. Preferably, before the reaction, both the glycidyl methacrylate and the functional monomer are treated to remove polymerization inhibitors and trace amounts of moisture are removed by molecular sieve drying, vacuum drying or inert gas purging. Preferably, the prepolymer retains 10%-60% of the epoxy functional side groups derived from glycidyl methacrylate (GMA), more preferably 20%-50%; Further optimized, the monomer conversion rate of the control system is 15-40%; More preferably, the free radical initiator is one or more of azobisisobutyronitrile, benzoyl peroxide, and ester peroxide initiators; More preferably, the amount of the free radical initiator is 0.1-2.0 wt% of the mass of glycidyl methacrylate monomer; More preferably, the organic solvent is selected from one or more of acetonitrile, tetrahydrofuran, and ethyl acetate; More preferably, when the glycidyl methacrylate, fluorinated functional monomer, free radical initiator, and organic solvent are mixed, the solid content of the system is controlled to be 10-40 wt%. More preferably, the inert atmosphere is a nitrogen atmosphere or an argon atmosphere; More preferably, the reaction system needs to be stirred in an inert atmosphere for 20-60 minutes before the free radical prepolymerization; More preferably, the temperature of the free radical prepolymerization is 60-70°C, and the time of the free radical prepolymerization is 1-4 hours; In this invention, the stirring deoxygenation can reduce the inhibitory effect of oxygen on the free radical prepolymerization reaction; in the free radical copolymerization process in step S1, by controlling the feeding ratio of glycidyl methacrylate and fluorinated functional monomers and the degree of copolymerization reaction, the obtained prepolymer has a suitable molecular weight, good solubility and a certain number of epoxy functional side groups, providing reaction sites for in-situ ring-opening crosslinking in the subsequent electrolyte environment; by controlling the low conversion rate (total monomer polymerization conversion rate, conversion rate test method and specific values ​​are detailed in Examples 1-4), the obtained glycidyl methacrylate prepolymer maintains an appropriate molecular weight and good solubility, avoiding premature gelation of the system or excessively high molecular weight leading to difficulty in subsequent powder dispersion.

[0012] More preferably, the fluorinated functional monomer is added dropwise to the glycidyl methacrylate prepolymer mother liquor in solution form and mixed thoroughly. More preferably, the dropping time is 0.5-3 hours, and the system temperature is maintained at 60-70°C during the dropping process. After the dropping is completed, the reaction is continued at this temperature for 3-8 hours. More preferably, the fluorinated functional monomer is selected from fluorinated acrylate monomers, fluorinated amide monomers, and perfluorinated aromatic monomers containing free radical polymerizable groups; More preferably, the fluorinated acrylate monomer is 2,2,2-trifluoroethyl acrylate or hexafluoroisopropyl methacrylate; More preferably, the fluorinated amide monomer is selected from trifluoroacetamide monomers; More preferably, the trifluoroacetamide monomer is a trifluoroacetamide derivative containing a free radical polymerizable unsaturated double bond or a trifluoroacetamide derivative containing a ring-opening reaction with a glycidyl methacrylate epoxy group; More preferably, the perfluoroaromatic monomer containing free radical polymerizable groups is a perfluoroaromatic derivative containing free radical polymerizable unsaturated double bonds, or a perfluoroaromatic derivative containing a ring-opening reaction with glycidyl methacrylate epoxy groups. In this invention, the content of free radical polymerizable unsaturated double bonds in the final prepolymer powder is adjusted by controlling the conversion rate of glycidyl methacrylate prepolymerization reaction and the degree of functional monomer grafting.

[0013] The content of unsaturated double bonds that can be polymerized by free radicals in the thermally crosslinkable prepolymer powder is 0.05-1.5 mmol / g, preferably 0.1-1.0 mmol / g. When the content of unsaturated double bonds is less than 0.05 mmol / g, the degree of crosslinking of the gel network formed during the subsequent thermally initiated crosslinking process is insufficient, making it difficult to effectively fix the liquid electrolyte. When the content of unsaturated double bonds is greater than 1.5 mmol / g, it is easy to lead to excessively high crosslinking density, reducing electrolyte wettability and lithium-ion transport capacity. Therefore, by controlling the content of unsaturated double bonds in the final product within the above range, both the stability of the semi-solid gel network and the ion transport performance can be taken into account.

[0014] In this invention, fluorinated functional monomers are introduced into the glycidyl methacrylate polymer chain segment via free radical copolymerization. Since the fluorinated functional monomers have different electronic structures and polar groups, the copolymerization can endow the prepolymer with different interface regulation, high voltage stability and lithium ion transport regulation capabilities.

[0015] In this invention, the final product possesses both a "functional side-chain regulated structure" and an "epoxy in-situ crosslinking structure." The functional side chains improve electrode / electrolyte interface stability, high voltage tolerance, and lithium-ion migration behavior; the epoxy functional side groups promote ring-opening crosslinking in the electrolyte environment through the active components, thereby forming a stable three-dimensional gel network. Specifically: The glycidyl methacrylate molecule contains both a methacrylate double bond and an epoxy group. The double bond can participate in the prepolymerization reaction to form a backbone; the epoxy group can serve as a subsequent functionalization reaction site to introduce some functional side chains or introduce unsaturated double bonds that can be polymerized again. In this invention, glycidyl methacrylate plays three roles: backbone construction, grafting functional side chains, and post-crosslinking interface construction. Fluorinated acrylate monomers can form fluorinated graft or copolymer prepolymer structures with glycidyl methacrylate under free radical conditions. Their fluorinated side chains can reduce the interfacial energy between the electrode and the electrolyte, improve the dispersion, wetting and swelling behavior of the prepolymer powder in carbonate electrolyte, and at the same time improve the antioxidant stability of the high voltage positive electrode interface by utilizing the high bond energy of CF bond and the electron-withdrawing effect of fluorinated group. Trifluoroacetamide monomers can introduce strongly polar amide structures. The carbonyl group, amide nitrogen, and trifluoromethyl group in the amide structure have a synergistic effect, which is beneficial for regulating Li... + The surrounding localized solvation environment weakens the overcoordination of free solvent molecules, improves lithium-ion migration selectivity, and reduces concentration polarization during high-rate charge and discharge processes. Perfluoroaromatic monomers containing free radical polymerizable groups can introduce a rigid electron-withdrawing structure for perfluoroaromatics. This structure has high oxidation stability and strong electron absorption and withdrawal capabilities, which is beneficial for suppressing the continuous oxidative decomposition of the electrolyte at the interface of high-nickel ternary cathodes and promoting the formation of a denser and more stable CEI protective layer, thereby reducing interfacial side reactions and charge transfer resistance.

[0016] More preferably, the solution containing the thermally crosslinkable prepolymer is concentrated under reduced pressure. More preferably, the precipitation is achieved using a poor solvent, which is one or more of n-hexane, petroleum ether, diethyl ether, and methanol; More preferably, the precipitate is collected by filtration or centrifugation; More preferably, the washing process involves washing 2-4 times with a poor-quality solvent; More preferably, the drying is vacuum drying, the drying temperature is 40-60℃, and the drying time is 12-48 hours; More preferably, the pulverization is one of cryogenic pulverization and airflow pulverization; In this invention, the washing process removes unreacted functional monomers, free homopolymers, low-molecular-weight byproducts, and residual initiators, while drying reduces residual solvents and moisture to within the range required for electrolyte application. After drying, the blocky, flocculent, or granular prepolymer is pulverized and sieved to obtain thermally crosslinkable prepolymer powder with a particle size of 1-20 μm. The obtained powder should be stored under light-protected, low-temperature, dry, and inert atmosphere or sealed conditions to avoid moisture absorption by the prepolymer or unintended reactions of the epoxy functional groups.

[0017] The present invention also proposes a semi-solid gel electrolyte, which includes a basic liquid electrolyte, the thermally crosslinkable prepolymer powder, and an active component that promotes the epoxy ring-opening reaction; the semi-solid gel electrolyte is formed by in-situ ring-opening crosslinking of the epoxy functional side groups in the thermally crosslinkable prepolymer powder in the electrolyte environment. Preferably, the active component that promotes the epoxy ring-opening reaction is selected from one or more of boron-containing lithium salts, fluorine-containing lithium salts, and Lewis acid type additives; More preferably, the active component that promotes the epoxy ring-opening reaction is lithium difluorooxalate borate (LiDFOB). The semi-solid gel electrolyte forms a three-dimensional gel network through in-situ ring-opening crosslinking of the epoxy function in the thermally crosslinkable prepolymer powder under the promotion of lithium salt additives such as LiDFOB. More preferably, the ring-opening reaction ratio is 5-50%, more preferably 10-30%; In this invention, the ring-opening reaction ratio refers to the proportion of the number of moles of epoxy groups participating in the ring-opening reaction to the total number of moles of reactive epoxy groups in the prepolymer, rather than the proportion of the total mass of the prepolymer.

[0018] More preferably, the amount of the thermally crosslinkable prepolymer powder added is 0.5-2 wt% of the mass of the base liquid electrolyte, more preferably 0.5-1.5 wt%. More preferably, the amount of the active component that promotes the epoxy ring-opening reaction added is 0.1-5 wt% of the mass of the basic liquid electrolyte, preferably 0.5-3 wt%.

[0019] More preferably, the amount of the thermally crosslinkable prepolymer powder added is 1.0 wt% of the mass of the base liquid electrolyte; More preferably, the basic liquid electrolyte is an electrolyte system in which lithium salt is dissolved in a carbonate solvent; More preferably, the base liquid electrolyte is 1 M LiPF6, the solvent system is EC / EMC / DMC=1:1:1, and it contains 5 wt% FEC + 1 wt% VC; More preferably, the in-situ polymerization crosslinking temperature is 60°C, and the in-situ polymerization crosslinking time is 6-8 hours; In this invention, the thermally crosslinkable prepolymer powder and lithium salt additives such as LiDFOB that promote the ring-opening reaction of epoxy are added to a basic liquid electrolyte, and then injected into the battery after stirring, ultrasonication, or high-speed dispersion. The prepolymer powder is uniformly dispersed in the liquid electrolyte due to its micron-sized particle size and functional side chains. Subsequently, the electrolyte gradually wets the interior of the prepolymer particles, creating a reaction environment between the epoxy groups and LiDFOB. Under heating conditions, the epoxy groups undergo in-situ ring-opening crosslinking, forming a three-dimensional gel network between different prepolymer molecular chains, thereby fixing the liquid electrolyte within the polymer network structure to obtain a semi-solid gel electrolyte.

[0020] This gel network can immobilize part of the liquid electrolyte, reduce the continuous side reactions of the electrolyte at the electrode interface, and maintain the high lithium-ion transport capacity of the base carbonate electrolyte. Since the amount of prepolymer powder added is very small, it will not significantly dilute the base electrolyte or significantly sacrifice rate performance.

[0021] This invention also proposes the application of the above-mentioned thermally crosslinkable prepolymer powder or the thermally crosslinkable prepolymer powder prepared by the above method in lithium-ion batteries. This powder undergoes in-situ polymerization and crosslinking inside the battery to form a semi-solid gel electrolyte, which can improve the interfacial stability, high voltage stability, and 2C fast-charge cycle performance of the high-nickel ternary cathode system under low addition conditions.

[0022] Beneficial effects of this invention: (1) In this invention, glycidyl methacrylate is used as the backbone monomer. Its methacrylate double bond participates in the free radical copolymerization reaction as a subsequent crosslinking reaction site to realize the introduction of functional side chains and the construction of gel network, so that the prepolymer powder has both structural designability, powder processability and subsequent crosslinkability. (2) The prepolymer powder provided by the present invention has both functional side chains and epoxy crosslinking sites. The functional side chains are used to improve interface stability, high voltage stability and lithium ion migration behavior. The epoxy groups undergo in-situ ring-opening crosslinking under the promotion of active components such as LiDFOB to form a stable three-dimensional gel network, which solves the problem that traditional functional polymer additives are difficult to achieve both low addition amount gelation and interface stability improvement. (3) The prepolymer powder obtained by the present invention is a micron-sized free-flowing powder, which can be added to the basic liquid electrolyte at a low addition amount of about 1.0 wt%, without significantly reducing the effective lithium salt concentration and ion transport capacity in the electrolyte, and at the same time can realize the transformation of liquid electrolyte into semi-solid gel electrolyte. (4) This invention utilizes the epoxy functional groups in the prepolymer to achieve in-situ ring-opening crosslinking inside the battery under the promoting effect of active components such as LiDFOB, so that the liquid electrolyte is transformed into a semi-solid gel electrolyte. This process does not require the addition of a high proportion of small molecule polymer monomers, nor does it rely on simple physical thickening, and can obtain a more stable three-dimensional crosslinking structure. (5) Different functional side chains of prepolymer powder can be controlled for different failure problems in ternary fast charging system. It is especially suitable for high nickel 811 ternary cathode system and 2C fast charging application scenario. Under 2C charging and 1C discharging conditions, it can effectively suppress interfacial side reactions and impedance growth under high rate conditions, showing better cycle stability, higher oxidation initiation voltage and lower interfacial impedance. Attached Figure Description

[0023] Figure 1 The normalized signal-retention time curves for samples 1 through 5 are shown. Figure 2 The dw / dlogM-molecular weight distribution curves for samples 1-5 are shown. Figure 3 Volume distribution diagram of P-1 laser-etched particle size of thermally crosslinkable prepolymer powder; Figure 4 The images show the molecular structure and nuclear magnetic resonance spectrum of the thermally crosslinkable prepolymer powder P-1. Figure 4 A is the molecular structure diagram of the powder. Figure 4 B is the powder 1 1H NMR spectrum (CDCl3 solvent) Figure 4 C is the powder 19F NMR spectrum (CDCl3 solvent); Figure 5 The images show the molecular structure and nuclear magnetic resonance spectrum of the thermally crosslinkable prepolymer powder P-2. Figure 5 A is the molecular structure diagram of the powder. Figure 5 B is the powder 1 1H NMR spectrum (CDCl3 solvent) Figure 5 C is the powder 19 F NMR spectrum (CDCl3 solvent); Figure 6 The images show the molecular structure and nuclear magnetic resonance spectrum of the thermally crosslinkable prepolymer powder P-3. Figure 6 A is the molecular structure diagram of the powder. Figure 6 B is the powder 1 1H NMR spectrum (CDCl3 solvent) Figure 6 C is the powder 19 F NMR spectrum (CDCl3 solvent); Figure 7 The images show the molecular structure and nuclear magnetic resonance spectrum of the thermally crosslinkable prepolymer powder P-4. Figure 7 A is the molecular structure diagram of the powder. Figure 7 B is the powder 1 1H NMR spectrum (CDCl3 solvent) Figure 7 C is the powder 19 F NMR spectrum (CDCl3 solvent). Detailed Implementation

[0024] To facilitate understanding of the present invention, a more comprehensive description will be provided below with reference to specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a more thorough and complete understanding of the disclosure of the present invention.

[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention.

[0026] The technical solution of the present invention will now be described more clearly and completely with reference to specific embodiments and comparative examples.

[0027] Example 1 This embodiment proposes a thermally crosslinkable prepolymer powder, the preparation method of which includes the following steps: (1) GMA (glycidyl methacrylate) and TFEA (2,2,2-trifluoroethyl acrylate) after being dried by removing polymerization inhibitors and molecular sieves were dissolved in acetonitrile to form a homogeneous system with a solid content of 20 wt%, wherein the molar ratio of GMA to TFEA was 8:2. After stirring and deoxygenating for 30 min under nitrogen protection, 1 wt% of AIBN (azobisisobutyronitrile) was added as a free radical initiator. The system was then heated to 65 °C and reacted for 3 h. The degree of polymerization was controlled so that a certain proportion of epoxy functional side groups were retained in the obtained copolymer to obtain a GMA-TFEA copolymer prepolymer solution with fluorinated alkyl ester functional side chains. In this study, the conversion ratio of monomers to polymers was calculated by measuring the mass ratio of unreacted volatile monomers to polymers in the reaction system at the reaction endpoint. The total monomer polymerization conversion rate in Example 1 was 28.5%, determined by the gravimetric solids content method. (2) After the above GMA-TFEA copolymer prepolymer solution containing fluorinated alkyl ester functional side chain is concentrated under reduced pressure, it is added dropwise to n-hexane for precipitation. The precipitate is collected by filtration and washed three times with n-hexane to remove unreacted monomers, low molecular weight by-products and residual initiators. (3) The washed precipitate was dried under vacuum at 50°C for 24 h, and then subjected to low-temperature pulverization and sieving to obtain GMA-TFEA type thermally crosslinkable prepolymer powder with a particle size of 1-20 μm. This sample was designated as P-1.

[0028] Example 2 This embodiment proposes a thermally crosslinkable prepolymer powder, the preparation method of which includes the following steps: (1) GMA (glycidyl methacrylate) and HFA (hexafluoroisopropyl methacrylate) after being treated with the removal of polymerization inhibitor and molecular sieve were dissolved in acetonitrile to form a homogeneous system with a solid content of 20 wt%, wherein the molar ratio of GMA to HFA was 8:2. After stirring and deoxygenating for 30 min under nitrogen protection, AIBN (azobisisobutyronitrile) with a total monomer mass of 1 wt% was added as a free radical initiator. The system was then heated to 65℃ and reacted for 3 h. The degree of polymerization was controlled so that a certain proportion of epoxy functional side groups were retained in the resulting copolymer to obtain a GMA-HFA copolymer prepolymer solution containing hexafluoroisopropyl methacrylate functional side chains. In this study, the conversion ratio of monomers to polymers was calculated by measuring the mass ratio of unreacted volatile monomers to polymers in the reaction system at the reaction endpoint. The total monomer polymerization conversion rate in Example 2 was 26.2%, determined by the gravimetric solids content method. (2) After the above GMA-HFA copolymer prepolymer solution containing hexafluoroisopropyl methacrylate functional side chain is concentrated under reduced pressure, it is added dropwise to n-hexane for precipitation. The precipitate is collected by filtration and washed three times with n-hexane to remove unreacted monomers, low molecular weight by-products and residual initiators. (3) The washed precipitate was dried under vacuum at 50°C for 24 h, and then subjected to low-temperature pulverization and sieving to obtain GMA-HFA type thermally crosslinkable prepolymer powder with a particle size of 1-20 μm. This sample was designated as P-2.

[0029] Example 3 This embodiment proposes a thermally crosslinkable prepolymer powder, the preparation method of which includes the following steps: (1) GMA (glycidyl methacrylate) and TFEAm (N-(2,2,2-trifluoroethyl)acrylamide) after being dried by removing polymerization inhibitors and molecular sieves were dissolved in acetonitrile to form a homogeneous system with a solid content of 20 wt%, wherein the molar ratio of GMA to TFEAm was 8:2. After stirring and deoxygenating for 30 min under nitrogen protection, 1 wt% of AIBN (azobisisobutyronitrile) was added as a free radical initiator. The system was then heated to 65 °C and reacted for 3 h. By controlling the degree of polymerization, a certain proportion of epoxy functional side groups were retained in the obtained copolymer to obtain a GMA-TFEAm copolymer prepolymer solution containing trifluoroacetamide functional side chains. In this study, the conversion ratio of monomers to polymers was calculated by measuring the mass ratio of unreacted volatile monomers to polymers in the reaction system at the reaction endpoint. The total monomer polymerization conversion rate in Example 3 was 31.0%, determined by the gravimetric solids content method. (2) After the above GMA-TFEAm copolymer prepolymer solution containing trifluoroacetamide functional side chain is concentrated under reduced pressure, it is added dropwise to n-hexane for precipitation. The precipitate is collected by filtration and washed three times with n-hexane to remove unreacted monomers, low molecular weight by-products and residual initiators. (3) The washed precipitate was dried under vacuum at 50°C for 24 h, and then subjected to low-temperature pulverization and sieving to obtain GMA-TFEAm type thermally crosslinkable prepolymer powder with a particle size of 1-20 μm. This sample was designated as P-3.

[0030] Example 4 This embodiment proposes a thermally crosslinkable prepolymer powder, the preparation method of which includes the following steps: (1) GMA (glycidyl methacrylate) and PFPA (pentafluorophenyl acrylate) after being treated with inhibitor removal and molecular sieve drying were dissolved in acetonitrile, wherein the molar ratio of GMA to PFPA was 8:2, forming a homogeneous system with a solid content of 20 wt%. After stirring and deoxygenating for 30 min under nitrogen protection, 1 wt% of AIBN (azobisisobutyronitrile) was added as a free radical initiator. The system was then heated to 65℃ and reacted for 3 h. The degree of polymerization was controlled to obtain a GMA-PFPA copolymer prepolymer solution containing epoxy functional side groups. In this study, the conversion ratio of monomers to polymers was calculated by measuring the mass ratio of unreacted volatile monomers to polymers in the reaction system at the reaction endpoint. The total monomer polymerization conversion rate in Example 4 was 24.8%, determined by the gravimetric solids content method. (2) After the reaction is completed, the above copolymer prepolymer solution is concentrated under reduced pressure and added dropwise to n-hexane for precipitation. The precipitate is collected by filtration and washed three times with n-hexane to remove unreacted monomers, oligomers and residual initiators. (3) The washed precipitate was dried under vacuum at 50°C for 24 h. After low-temperature crushing and sieving, GMA-PFPA type thermally crosslinkable prepolymer powder with a particle size of 1-20 μm was obtained, which was designated as P-4.

[0031] The performance of the samples and test batteries obtained by this invention is tested, specifically including: Test molecular weight related data: To investigate the effects of parameters in the preparation method on the performance of GMA-TFEA type thermally crosslinkable prepolymer powder, different GMA-TFEA type thermally crosslinkable prepolymer powders (denoted as Sample 1-Sample 5) were obtained by adjusting the prepolymerization time and initiator concentration. GPC tests were performed on Samples 1-5 (test conditions: THF mobile phase, flow rate 1.0 mL / min, column temperature 35℃, RID differential detector, standard: polystyrene (PS) standard; results are shown below). Figure 1 and Figure 2 As shown; The preparation methods for samples 1-5 were the same as in Example 1, except for differences in prepolymerization time and initiator concentration parameters. The specific differences and corresponding test results are shown in Table 1. Table 1. Process parameters and corresponding molecular weight data for samples 1-5

[0032] Figure 1 and Figure 2 The GPC test results for samples 1-5 are shown in the figure (including the normalized signal-retention time curve and the dw / dlogM-molecular weight distribution curve). Test granularity related data: The particle size of the thermally crosslinkable prepolymer powder P-1 obtained in Example 1 was analyzed using a laser particle size analyzer. The test conditions were: isopropanol as the dispersion medium, ultrasonic dispersion for 3 min, and the laser particle size analyzer's test range was 0.1-1000 μm. Figure 3 Table 2 shows the volume distribution of the thermally crosslinkable prepolymer powder P-1 and the particle size distribution characteristics of the thermally crosslinkable prepolymer powder P-1. Table 2. Particle size distribution characteristics of thermally crosslinkable prepolymer powder P-1

[0033] Depend on Figure 3 As shown in Table 2, the particle size distribution of this powder ranges from 1 to 10 μm, and the D50 is about 4 to 6 μm. It is uniformly distributed and suitable for rapid and uniform dispersion in electrolyte systems. The specific structure and content of functional groups / chemical bonds contained in the product of this invention were tested: Figures 4-7 NMR spectroscopy of thermally crosslinkable prepolymer powders P-1, P-2, P-3, and P-4 1 H 19 The F-test results and the 1H NMR spectroscopy results show that P-1, P-2, P-3, and P-4 all retain the characteristic signals of epoxy methylene, epoxy methine, and aliphatic protons in the polymer backbone of the GMA structural unit, indicating that the epoxy functional side groups in GMA are effectively preserved during the copolymerization process. Simultaneously, characteristic proton signals corresponding to the structures of the functional monomers TFEA, HFA, TFEAm, and PFPA were observed in each sample, indicating that different functional monomers have been successfully introduced into the GMA polymer chain segments via free radical copolymerization, forming copolymer prepolymer structures with fluorinated alkyl esters, fluorinated amides, or perfluoroaryl functional side chains. These results demonstrate that the prepared prepolymer powder simultaneously possesses functional side chain structures and active epoxy functional groups that can participate in subsequent epoxy ring-opening crosslinking.

[0034] Using high-resolution proton nuclear magnetic resonance (1H-NMR) quantitative integration, the actual retention ratio of epoxy side groups after reaction was calculated by comparing the absorption peak area of ​​epoxy methylene / epoxy methine protons (chemical shift approximately 2.6-3.2 ppm) with that of aliphatic protons in the main chain (chemical shift approximately 0.8-2.1 ppm). The calculation formula is: epoxy side group retention ratio (%) = (number of measured epoxy side groups in the prepolymer / number of initial GMA feed moles) × 100%. The test and calculation results are shown in Table 3. Table 3. Measured epoxy side group retention ratios of thermally crosslinkable prepolymer powders P-1, P-2, P-3, and P-4

[0035] The double bond content was determined using Fourier transform infrared spectroscopy (FTIR) with internal standard method combined with bromine addition titration. Specifically, the dried prepolymer powder was prepared into KBr tablets, and Fourier transform infrared spectroscopy was used at 4000-400 cm⁻¹. -1 Spectral scanning within the range, measurement at 1638 cm⁻¹ -1 The absorption peak area of ​​the methacrylate double bond (C=C) was used as the internal standard, and the absolute molar number of the residual double bond was determined by the bromine addition titration method (the prepolymer is dissolved in chloroform, excess iodine bromide solution is added and reacted in the dark, and then back titrated with sodium thiosulfate standard solution). Calculation formula: Unsaturated double bond molar content (mmol / g) = Total number of double bonds converted from iodine bromide consumption (mmol) / Prepolymer sample mass (g). The test results are shown in Table 4. Table 4. Double bond content of P-1, P-2, P-3 and P-4 in thermally crosslinkable prepolymer powders

[0036] As can be seen from Table 4, the double bond content of thermally crosslinkable prepolymer powders P-1, P-2, P-3 and P-4 all meet the range specified in the aforementioned instructions (0.05-1.5 mmol / g). Preparation of test cells: To investigate the minimum addition amount of the thermally crosslinkable prepolymer powder of the present invention required for effective gelation, the thermally crosslinkable prepolymer powder P-1 prepared in Example 1 was added to a basic electrolyte (1M LiPF6 EC / EMC / DMC = 1:1:1 + 5 wt% FEC + 1 wt% VC) + 1 wt% LiDFOB at addition amounts of 0 wt%, 0.5 wt%, 1.0 wt%, 2.0 wt%, 3.5 wt%, 5.0 wt%, and 6.5 wt%, respectively. After stirring and ultrasonic dispersion, the electrolyte was injected into a battery (a battery composed of a high-nickel 811 ternary cathode and a lithium metal anode) and heated at 60°C for 6 hours. h, an in-situ cross-linked semi-solid gel electrolyte was formed, in which the blank control group was Comparative Example 1, denoted as Base; the addition amount of 0.5 wt% was denoted as Example 1a, the addition amount of 1.0 wt% was denoted as Example 1, the addition amount of 2.0 wt% was denoted as Example 1b, the addition amount of 3.5 wt% was denoted as Example 1c, the addition amount of 5.0 wt% was denoted as Example 1d, and the addition amount of 6.5 wt% was denoted as Comparative Example 2; the electrochemical performance and electrolyte state of the battery under test were tested under different addition amounts of thermally cross-linkable prepolymer powder P-1 in the battery, and the specific results are shown in Table 5; Table 5. Electrochemical performance and electrolyte state of sample P-1 at different addition amounts in the battery

[0037] As shown in Table 5, the electrolyte can be effectively gelled without phase separation or performance degradation within the addition range of 0.5-5 wt%. Among them, the electrolyte gel state is the most uniform and stable and the electrochemical performance is the best when the addition amount is 1.0 wt%. The thermally crosslinkable prepolymer powders P-1 to P-4 prepared in Examples 1-4 above were added to the basic electrolyte (1M LiPF6 EC / EMC / DMC=1:1:1 + 5 wt% FEC + 1 wt% VC) + 1 wt% LiDFOB at an addition amount of 1 wt%. After stirring and ultrasonic dispersion, the electrolyte was injected into a battery (a battery composed of a high-nickel 811 ternary cathode and a lithium metal anode). The battery was heated at 60°C for 6 h to form an in-situ crosslinked semi-solid gel electrolyte. The resulting test batteries were designated as Cell-P-1, Cell-P-2, Cell-P-3 and Cell-P-4, respectively. The test results are shown in Table 6. The test conditions for the battery are as follows: constant current charging at 2C rate and constant current discharging at 1C rate at 25℃, with the voltage range set to 2.8-4.3 V.

[0038] Table 6 Performance test results of Cell-P-1, Cell-P-2, Cell-P-3, Cell-P-4 and Base

[0039] The test results in Table 6 show that, compared with Base, Cell-P-1, Cell-P-2, Cell-P-3, and Cell-P-4 all exhibit higher 200-cycle capacity, capacity retention, oxidation initiation voltage, and lower Rs, Rsei, and Rct, indicating that the prepolymer powder can effectively improve the interfacial stability, high voltage stability, and charge transfer kinetics of the semi-solid gel electrolyte.

[0040] In Cell-P-1, the introduction of flexible fluorinated TFEA side chains improves the interfacial compatibility between the prepolymer and the electrolyte, and the fluorinated structure enhances interfacial stability under high voltage conditions, thus exhibiting superior cycle performance and lower interfacial impedance compared to Base. In Cell-P-2, the HFA side chains have a higher fluorine content, further enhancing the chemical stability of the polymer network and the ability to regulate the electrode / electrolyte interface, thus further improving its cycle retention and impedance performance. In Cell-P-3, the polar amide structure in the trifluoroacetamide side chains is beneficial for regulating Li +The localized solvation environment improves lithium-ion transport behavior, thereby further reducing interfacial polarization and improving capacity retention. In Cell-P-4, the perfluoroaromatic structure of PFPA has strong electron absorption and withdrawal capabilities and high oxidation stability, which can further improve interfacial stability under high voltage conditions and suppress electrolyte oxidation side reactions. Therefore, it performs best in terms of capacity retention, oxidation initiation voltage and Rct reduction.

[0041] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A thermally crosslinkable prepolymer powder, characterized in that, The thermally crosslinkable prepolymer powder comprises a polymer backbone formed by free radical copolymerization of glycidyl methacrylate and fluorinated functional monomers; The polymer backbone retains epoxy functional side groups; The polymer backbone is connected to at least one functional side chain selected from fluorinated alkyl ester side chains, fluorinated amide side chains, and perfluorinated aryl side chains; The prepolymer retains 10%-60% of the epoxy functional side groups derived from glycidyl methacrylate (GMA).

2. The thermally crosslinkable prepolymer powder according to claim 1, characterized in that, The number-average molecular weight (Mn) of the thermally crosslinkable prepolymer powder is 3000-20000 g / mol, the weight-average molecular weight (Mw) of the thermally crosslinkable prepolymer powder is 8000-60000 g / mol, and the molecular weight distribution (PDI) of the thermally crosslinkable prepolymer powder is 1.5-3.

5.

3. The thermally crosslinkable prepolymer powder according to claim 1 or 2, characterized in that, The particle size of the thermally crosslinkable prepolymer powder is 1-20 μm; the D50 of the thermally crosslinkable prepolymer powder is 3-8 μm.

4. A method for preparing the thermally crosslinkable prepolymer powder according to any one of claims 1-3, characterized in that, Includes the following steps: S1. Glycidyl methacrylate, fluorinated functional monomer, free radical initiator and organic solvent are mixed and prepolymerized under an inert atmosphere. The polymerization conversion rate is controlled at 10-50% to obtain a fluorinated prepolymer solution containing epoxy functional side groups. S2. The obtained fluorinated prepolymer solution containing epoxy functional side groups is concentrated, precipitated, washed, dried, pulverized and sieved to obtain the thermally crosslinkable prepolymer powder.

5. The method for preparing the thermally crosslinkable prepolymer powder according to claim 4, characterized in that, The fluorinated functional monomer is selected from one or more of fluorinated acrylate monomers, fluorinated amide monomers, and perfluorinated aromatic monomers containing free radical polymerizable groups.

6. A semi-solid gel electrolyte, characterized in that, The semi-solid gel electrolyte comprises a basic liquid electrolyte, the thermally crosslinkable prepolymer powder of claim 1, and an active component that promotes the epoxy ring-opening reaction; the semi-solid gel electrolyte is formed by in-situ ring-opening crosslinking of the epoxy functional side groups in the thermally crosslinkable prepolymer powder of claim 1 in the basic liquid electrolyte.

7. The semi-solid gel electrolyte according to claim 6, characterized in that, The amount of the thermally crosslinkable prepolymer powder added is 0.5-5 wt% of the mass of the basic liquid electrolyte; the amount of the active component that promotes the epoxy ring-opening reaction added is 0.1-5 wt% of the mass of the basic liquid electrolyte.

8. The semi-solid gel electrolyte according to claim 6 or 7, characterized in that, The active component that promotes the ring-opening reaction of epoxy is selected from one or more of boron-containing lithium salts, fluorine-containing lithium salts, and Lewis acid type additives.

9. The application of a thermally crosslinkable prepolymer powder according to any one of claims 1-3 or a thermally crosslinkable prepolymer powder prepared by the preparation method according to claim 4 or 5 in a lithium-ion battery.